Do exílio à missão: congregações religiosas femininas francesas no Brasil - século XIX - Colombo, Maria Alzira da Cruz (2018)
The purpose of this article is to analyze the link between the political situation in France during the 3rd Republic (1870-1914) and the progressive marginalization that the pedagogical religious congregations have suffered and that eventually led to their emigration to Brazil, from the 19th century on. My intention is to study not only the historical context, but also the sociological, cultural and political background in France in that period, that drove France to secularization, as a result of the Jules Ferry Laws in 1880. It’s also my intention to highlight the dissolution of religious schools in France and, on the other hand, the possibility of emigration, which consequently brought educational and cultural evolution to the feminine youth in Brazil during the Imperial and Republican periods. Finally, I’ve focused my research in the particular case of the congregation Our Lady of Sion as a paradigmatic example of the sister’s congregations that left France during that period and founded colleges in many cities in the southeast region of Brazil. This analysis shows the pioneering spirit of women from those important missionary congregations